Peningkatan Kemampuan Penjumlahan Melalui Model Pembelajaran Project Based Learning bagi Anak Tunagrahita Ringan - Sembiring, Anita Br; Ardisal, Ardisal (Universitas Negeri Padang, 2023)
This research is motivated by the problems found in SLB Merlung Jambi in mild mental retardation class VC who have problems with addition. From the results of the assessment it was found that students had difficulty in the summing activity of the downward series. This study aims to improve the process and learning outcomes of summation material through the Project Based Learning learning model. The research method used was classroom action research consisting of 2 cycles. Based on the results of the research, the use of the Project Based Learning learning model is effective for increasing the ability to sum the downward series. This can be seen from the increased student learning outcomes in each cycle